IMPACT OF OWNERSHIP STRUCTURE AND DIVERSIFICATION ON FIRM VALUE: EVIDENCE FROM THE SHARIAH AND NON-SHARIAH COMPLIANT REITS COMPANIES - Noryati Ahmad; Siti Fathonah Mohd Nafiah (Journal of Islamic Management Studies, 2020)
Firm value is affected by many factors among them are management itself, ownership structure of the company, and diversification strategy adopted by the company. Therefore, this study attempts to investigate and compare the impact of ownership structure and diversification on firm value between Shariah and non-Shariah compliant REITs companies in Malaysia. The study uses annual data that cover the period of 2006 until 2013. Empirical evidences indicate that all ownership structure measures; namely, insider ownership, institutional ownership, foreign ownership, shareholder dispersion have significant and positive impact on firm value. Furthermore, results suggest that diversified Shariah and non-Shariah compliant REITs have higher performance relative to those that do not diversified.